Exponential stability of nontrivial solutions of stochastic differential equations - Tran Thi Thu Lan; Nguyen Hai Dang (Scientia, 2025)
This paper is concerned with the exponential stability of nontrivial solutions of stochastic differential equations. In this paper, we give new criteria for the exponential stability for stochastic differential equations without the trivial solution.